2016
DOI: 10.1161/hypertensionaha.115.06814
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cost-Effectiveness of Conservative or Intensive Blood Pressure Treatment Guidelines in Adults Aged 35–74 Years

Abstract: Abstract-The population health effect and cost-effectiveness of implementing intensive blood pressure goals in highcardiovascular disease (CVD) risk adults have not been described. Using the CVD Policy Model, CVD events, treatment costs, quality-adjusted life years, and drug and monitoring costs were simulated over 2016 to 2026 for hypertensive patients aged 35 to 74 years. We projected the effectiveness and costs of hypertension treatment according to the 2003 Joint National Committee (JNC)-7 or 2014 JNC8 gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Based on our sensitivity analysis, the true cost‐effectiveness of our approach to diagnosis and treatment of SHHD likely sits between $20,000 and $30,000 per year—a figure that is similar to recently published data by Moise et al that found more intensive BP control to be cost‐effective at <$50,000 per QALY for management of HTN, particularly in patients with cardiovascular disease, chronic kidney disease, and a 10‐year cardiovascular disease risk > 15%. In a recent perspective piece, Neumann et al argue that the $50,000 per QALY measure may indeed be too low.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Based on our sensitivity analysis, the true cost‐effectiveness of our approach to diagnosis and treatment of SHHD likely sits between $20,000 and $30,000 per year—a figure that is similar to recently published data by Moise et al that found more intensive BP control to be cost‐effective at <$50,000 per QALY for management of HTN, particularly in patients with cardiovascular disease, chronic kidney disease, and a 10‐year cardiovascular disease risk > 15%. In a recent perspective piece, Neumann et al argue that the $50,000 per QALY measure may indeed be too low.…”
Section: Discussionsupporting
confidence: 80%
“…A threshold cost of $50,000 per QALY is the traditional benchmark for determining the value of care. Therefore, values at or below this were adopted in our study as the measure of cost‐effectiveness . The cost per QALY was modeled by the following mathematical equation, where 0.87 and 0.71 are used as standard utility values assigned to patients for whom chronic HF (the most likely adverse consequence of untreated SHHD) would or would not be prevented by treatment, respectively:CostQALY=Total cost)(QALYyearif effective×expected life span×probability of effectiveness2.047em2.047emtrue(QALYyearif not effective×expected life span×probability of not being effective2.047em2.047emtrue)=Total cost(0.87×20(%effective))+(0.71×20(1%effective))…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Moise and colleagues estimated more favorable ICERs for intensive control than for standard control among U.S. adults at high cardiovascular risk, but they did not define a high risk of cardiovascular disease strictly according to SPRINT eligibility criteria; in addition, they simulated only a 10-year time horizon and did not account for the costs of treating noncardiovascular diseases in their cost-effectiveness calculations. 31 Richman et al used a lifetime horizon, with their main cost-effectiveness estimate of approximately $24,000 per QALY gained, which was presumably based on lifetime persistence of the benefits of intensive control as defined in SPRINT. 32 Our base case assumed a reduction in treatment effects over time on the basis of standard practice for cost-effectiveness analysis of clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…16 A second recent cost-effectiveness analysis evaluated the cost-effectiveness of intensive blood pressure management in addition to current hypertension guidelines and concluded that intensive blood pressure management is cost-effective or cost-saving. 27 Our analysis adds to this body of literature by specifically incorporating the estimates of benefit and risk described in SPRINT and exploring the cost-effectiveness of intensive blood pressure management in older populations.…”
Section: Discussionmentioning
confidence: 99%